Effect of intense training on plasma leptin in male and female swimmers - Noland, R. C.; Baker, J. T.; Boudreau, S. R.; Kobe, R. W.; Tanner, C. J. M.; Hickner, R. C.; McCammon, M. R.; Houmard, J. A. (Medicine & Science in Sports & Exercise, 2001)
Purpose: The purpose of this study was to determine whether fasting plasma leptin concentration was altered with an increase in training volume in competitive male and female athletes. Methods: Intercollegiate male (N = 9) and female (N = 12) swimmers were examined during the preseason and at two times during the mid-season (mid-season 1 and mid-season 2) when training volume was relatively high (33,000 m.wk-1). Body composition (hydrostatic weighing), energy intake and expenditure, and fasting plasma leptin concentration were measured. Results In the women, there was a significant (P < 0.05) decline in fat mass (2 kg) with the increase in training volume, which was not accompanied by a reduction in fasting leptin (12.8 +/- 1.5 vs 11.0 +/- 1.2 vs 11.0 +/- 1.5 ng.mL-1 for preseason, mid-season 1, and mid-season 2, respectively). In the men, there were no significant changes in body composition, body mass, or fasting leptin (4.4 +/- 0.8 vs 4.3 +/- 0.8 vs 4.6 +/- 0.8 ng.mL-1, respectively). Conclusions: These findings suggest 1) plasma leptin is not sensitive to an increase in training volume and 2) leptin may not be indicative of changes in fat mass with an increase in training volume in female athletes. These data suggest that leptin may not be useful in monitoring relative training stress in athletes.